Tea Scale, Fiorinia theae Green (Insecta: Homoptera: Diaspididae) - Christian F. Miller (EDIS)
This document is EENY-250, one of a series of the Department of Entomology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date printed: November 2001.